Occurrence of marine plastic litter and plasticizers from touristic beaches of Arauco Gulf in Central Chile - Recabarren, Tatiana; Torres, Mariett; Gómez, Victoria; Jacobsen, Camila; Villablanca, Mathias; Ahrendt, Camila; da Silva Montes, Caroline; Galbán-Malagón, Cristóbal; Tombesi, Norma; Pozo, Karla (Marine pollution bulletin, 2024)
Marine plastic litter (MPL) was collected from beaches (n = 3) of the Arauco Gulf in central Chile in spring 2021 and summer 2022. MPL was analyzed for physical and chemical characteristics, and plasticizers were also screened using FTIR-ATR. Three hundred seventeen plastic items with an accumulated weight of 226.8 g were found. MPL densities ranged from 0.4 to 17.1 items m-2. Significant differences (p < 0.05) between seasons were observed for Arauco and Maule beaches, being ∼ten times higher in summer compared to spring. Solid pieces were the predominant shape, macroplastics were the most abundant (>2.5 cm), and white and blue colors were dominant. Polypropylene (52 %) and polyethylene (31 %) were the predominant polymers. Plasticizers (n = 3) were detected in the MPL in the study area (dioctyl phthalate, polybutene, and alpha-methylstyrene) for the first time. This study contributes new information related to MPL in coastal areas of central Chile and their chemical composition.
Keywords: Plasticizers; Chile; Plastic pollution; Polymer composition; Environmental Monitoring; Plastics; chemické látky znečišťující vodu; koupací pláže; Bathing Beaches; Beaches; Phthalates; změkčovadla; Water Pollutants, Chemical; plastické hmoty; monitorování životního prostředí